Functional consequences of the lack of amyloid precursor protein in the mouse dentate gyrus in vivo - Jedlička, Peter; Tschäpe, Jakob-Andreas; Hick, Meike; Müller, Ulrike C. (Experimental brain research, 2012)
The amyloid precursor protein (APP) plays a crucial role in the pathogenesis of Alzheimer’s disease. Here, we studied whether the lack of APP affects the synaptic properties in the dentate gyrus by measuring granule cell field potentials evoked by perforant path stimulation in anesthetized 9-11-month-old APP-deficient mice in vivo. We found decreased paired-pulse facilitation, indicating altered presynaptic short-term plasticity in the APP-deficient dentate gyrus. In contrast, excitatory synaptic strength and granule cell firing were unchanged in APP knockout mice. Likewise, long-term potentiation (LTP) induced by a theta-burst stimulation protocol was not impaired in the absence of APP. These findings suggest that the deletion of APP may affect presynaptic plasticity of synaptic transmission at the perforant path-granule cell synapse but leaves synaptic efficacy intact and LTP preserved, possibly due to functional redundancy within the APP gene family.
Published online 11 November 2011
Gesehen am 20.08.2018